Analisis Kepuasan Peserta Didik Kelas XI di Madrasah terhadap Materi Fiqh Berbasis Konten Instagram - Hariono, Fafia Nurlaili; Sulaikho, Siti (ISLAMIKA, 2024)
The aim of this research was to determine the satisfaction of class IX MTsN 3 Jombang students with Instagram content-based fiqh learning media. The results of this research will later be used as a benchmark for students' needs for fiqh learning videos based on Instagram content. The research carried out used quantitative methods. In this study, researchers used a sample of 30 class IX students at MTsN 3 Jombang. Of the 30 samples who had filled out the satisfaction questionnaire regarding fiqh learning videos based on Instagram content, 262% of the answers were found to agree that there was this fiqh learning content. In the Islamic jurisprudence learning process, MTsN 3 Jombang educators only use lecture and practice methods, making students bored and tend not to listen so that during practice students feel confused. Based on the results of the satisfaction questionnaire, 262% of students answered that they agreed to this learning video. Therefore, it is important for educators to improve their effectiveness when learning fiqh at MTsN 3 Jombang by trying learning methods based on Instagram content.